Analysis of Criminal Acts of Corruption of Village Funds Committed by the Geuchik of Paya Lipah Village, Bireuen Regency, Aceh - Rachmad, Nasril; Mandasari Saragih, Yasmirah (PT. Multidisciplinary Press Indonesia, 2024)
The criminal act of village fund corruption committed by the Geuchik of Gampong Paya Lipah, Bireuen Regency, Aceh, is a real example of abuse of authority that damages public trust in village officials. This article aims to analyze the factors that drive corruption in the management of village funds and its impact on village development and community welfare. This study uses a qualitative approach with a case study method, involving interviews with local residents, data collection from related agencies, and analysis of official documents. The results of the study indicate that weak supervision, lack of transparency in fund management, and low legal awareness among village officials are the main factors that trigger corruption. In addition, it was found that this corruption had a significant impact on the delay in the implementation of village development programs, loss of public trust, and increasing public dissatisfaction with the village government. This article also discusses the efforts that have been made by law enforcement officers and local governments in handling this case, and recommends preventive measures to prevent similar cases from recurring in the future. The conclusion of this analysis emphasizes the importance of strengthening the supervision system, increasing transparency, and legal education for village officials as an effort to create better village fund governance that is free from corrupt practices.